2006
DOI: 10.1021/es060923f
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol-Degrading Bacteria Isolated from Activated Sludge

Abstract: Fourteen phylogenetically diverse 17beta-estradiol-degrading bacteria (strains KC1-14) were isolated from activated sludge of a wastewater treatment plant. These isolates widely distributed among eight different genera--Aminobacter (strains KC6 and KC7), Brevundimonas (strain KC12), Escherichia (strain KC13), Flavobacterium (strain KC1), Microbacterium (strain KC5), Nocardioides (strain KC3), Rhodococcus (strain KC4), and Sphingomonas (strains KC8-KC11 and KC14)--of three Phyla: Proteobacteria, Actinobacteria,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
141
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(149 citation statements)
references
References 42 publications
6
141
2
Order By: Relevance
“…Aerobic incubation: The present study showed that aerobic incubation (1) degraded cEs (cE2, cE1 > cE3); and (2) transiently increased fEs concentrations (fE1, fE2 > fE3) and ensuing estrogenic activity in manure samples, possibly due to diverse groups of aerobic bacteria that activated (resulted in an increase in estrogenic activity) and/or hydrolyzed (resulted in a decrease in estrogenic activity) estrogens [66][67][68][69]. In aerobic environment, aerobic bacteria were several folds more active than anaerobic ones [70].…”
Section: Effects Of Aerobic and Anaerobic Digestions On Estrogen Concmentioning
confidence: 69%
“…Aerobic incubation: The present study showed that aerobic incubation (1) degraded cEs (cE2, cE1 > cE3); and (2) transiently increased fEs concentrations (fE1, fE2 > fE3) and ensuing estrogenic activity in manure samples, possibly due to diverse groups of aerobic bacteria that activated (resulted in an increase in estrogenic activity) and/or hydrolyzed (resulted in a decrease in estrogenic activity) estrogens [66][67][68][69]. In aerobic environment, aerobic bacteria were several folds more active than anaerobic ones [70].…”
Section: Effects Of Aerobic and Anaerobic Digestions On Estrogen Concmentioning
confidence: 69%
“…Chlorine treatment resulted in chlorinated E 1, E2, and EE 2 that were 1 × 10 3 to 1 × 10 4 more estrogenic than BPA as assessed by yeast two-hybrid assay, with the relative potency depending on the site of chlorination and the source of estrogen receptor (human or fish; medaka). Bacterial degradation of estrogens has been documented (25) and recent research has focused on identifying estrogen-degrading strains (26). Although microbes efficiently degrade estradiol to estrone, the latter is more persistent (26).…”
Section: Ppm)mentioning
confidence: 99%
“…Bacterial degradation of estrogens has been documented (25) and recent research has focused on identifying estrogen-degrading strains (26). Although microbes efficiently degrade estradiol to estrone, the latter is more persistent (26). However, some bacterial strains isolated from activated sludge were found to be capable of degrading estrone (27) and might prove useful as probiotics in waste digesters, but they would first need to be evaluated for strain safety, including assessment of toxicity and toxic product formation.…”
Section: Ppm)mentioning
confidence: 99%
“…The possibility to evolve bacterial-based process is still controversial. Among 14 bacterial strains isolated from activated sludge capable of reducing 17β-estradiol, only one degraded estrone, too (Yu et al 2007). …”
Section: Introductionmentioning
confidence: 99%